The National Blood Transfusion Service
1947-04 1947 1940s 4 pages Serum - the fluid separated from blood after it has clotted - also proved to be a valuable substitute for whole blood. It is more easily filtered than plasma, and has similar keeping properties. In 1940 an even better method was developed. It was found that liquid plasma and serum - could be dried into powders and could be stored for any length of time in any climate. The Rh Factor Early in 1940, a new factor, called the Rhesus or Rh factor was found in the red blood cells. This factor is present in the red cells of 85% of Europeans, who are termed Rh-positive: the remaining 15%, whose cells do not contain it, are termed Rh-negative. The Rh factor is of importance in transfusion because Rh-negative people may, under certain circumstances produce antibodies to it which appear in their blood and will destroy red blood cells containing the Rh factor. Such people are said to have been immunized, or sensitized to the Rh factor. Immunization may occur if an Rh-negative patient is transfused with blood from an Rh-positive donor. No harm usually results the first time such a transfusion is given, but if the Rh-negative person receives a second transfusion of Rh-positive blood, a reaction, which may be serious, may occur. Likewise, the Rh-negative wife of an Rh-positive husband, may bear an Rh-positive child. The mother may be immunized by the Rh factor present in her child before it is bom, and produce antibodies which pass into the child and, by destroying its red blood cells which contain the Rh factor, cause a serious form of anaemia, accompanied by jaundice (haemolytic disease of the newborn). It should be emphasized that only a small proportion of the off-spring of Rh-negative mothers and Rh-positive fathers, suffer from this disease, and that the disease usually appears only after a succession of healthy Rh-positive children have been born. It does not follow that, because the Rh groups of the mother and father differ in the way described, their children will be affected. The discovery of the Rh factor has made transfusion safer, and, by explaining the cause of this obscure form of anaemia in infants, has enabled appropriate treatment to be given. The Rh antibodies lose their effect within a few weeks of birth. Transfusion of Rh-negative blood will usually save the lives of seriously affected infants by helping them over this critical period. Moreover, it is now possible to avoid sensitizing women to the Rh factor by the transfusion of blood of the wrong Rh group: such immunization may cause anaemia and jaundice to appear in their earlier off-spring, who would have been healthy had the mother not become sensitized. If it can be determined which women are Rh-negative and whether these Rh-negative women are forming Rh antibodies, it would be possible to diagnose haemolytic disease during the ante-natal period. Preparations can thus be made to have suitable blood ready to transfuse the baby, and in severe cases the baby can be removed by premature delivery from the harmful effects of the mother's antibodies. Blood Products New experiments have also been made in the production of blood products. Fibrin Foam made from blood plasma can be used to control bleeding in operations where the tying of blood vessels is not advisable. It is also of great value in brain and spinal Surgery where nerve cells, once destroyed, would not grow again. Thrombin, also extracted from blood plasma is a valuable agent for clotting blood and can be used either alone or in conjunction with Fibrin Foam. 3. 292/845.2/4/13